The nationalism of Alexandre Levy em suas Variations sur un Thême Populaire Brésilien (Orfeu, 2016)
This article examines Alexandre Levy’s (1864 - 1892) nationalism through bibliographic research, comprising the historical context, a composer’s biographical sketch and the study of his correspondences with the ideals of modernity and national identity from “generation of 1870” andother contemporary intellectuals. Finally, it also collects relevant information and examines published comments about the Variations on a popular Brazilian theme (1887), besides accomplishing a brief musical analysis. The objective was to clarify the composer’s thought and his intents on writing the work in question. A musical nationalism that wasn’t peculiar to Alexandre Levy, but was shared by his contemporaries as well and which presents a prominent cosmopolite face has been unveiled.
Keywords: Alexandre Levy; Brazilian musical nationalism; Generation of 1870; Musicology